-5b-6=1-5(b+2)

Simple and best practice solution for -5b-6=1-5(b+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5b-6=1-5(b+2) equation:



-5b-6=1-5(b+2)
We move all terms to the left:
-5b-6-(1-5(b+2))=0
We calculate terms in parentheses: -(1-5(b+2)), so:
1-5(b+2)
determiningTheFunctionDomain -5(b+2)+1
We multiply parentheses
-5b-10+1
We add all the numbers together, and all the variables
-5b-9
Back to the equation:
-(-5b-9)
We get rid of parentheses
-5b+5b+9-6=0
We add all the numbers together, and all the variables
3!=0
There is no solution for this equation

See similar equations:

| (a+5)^3=0 | | 6=k+17 | | 7x-(8-3x)=2 | | 5/7x+29=57 | | 3a^2-24a=45 | | 6w+9=6w-15 | | 4(x-1)^2-3=0 | | (x+6)(-x+1)=0 | | 7(x+3)+6=-7(x-8) | | 9r+1=2r+22 | | x2+20=0 | | A=9/7(h-55) | | (6a-5)=4 | | 35=7+44b | | x2+10x+12=36 | | 2y^2-9y=-9 | | 1x+2x²=9 | | 8y-19=-19 | | 4x+2=(−8)+6x | | v+9/3=3 | | 464=8q | | 10x^2+7x+94=0 | | 9-r+12=-24 | | 5y+3=2/3 | | 6a^2=34a-48 | | 7x2-8x=0 | | 1/2+x=3/5 | | 3(x-1)^2+11=0 | | (x-7)(3x+2)(x+1)=0 | | 3(3x+1)=6x+14 | | 8y-19=(-19) | | 100/360=x/62.8 |

Equations solver categories